BAMOE EDUKASI UNTUK SEKOLAH AL-QORROBIYAH DESA SENDANG DAJAH (Lembaga Penelitian Dan Pengabdian Kepada Masyarakat Universitas 17 Agustus 1945 Surabaya, 2019)
The purpose of training is a activities of community servants where we have a reason why this Al-Qorrobiyah Foundation School is our target because this school, which is the largest foundation in Sendang Dajah Village, is still a problem with technological developments, for example the learning curriculum there is still using the Education Unit Level Curriculum (KTSP) 2014, while in University which has implemented the Education Curriculum 2019 (KP). The procedure for this training students will be explained about Ms.Office. After the material is explained, students will be accompanied one by one to work on sample problems, in order to measure students' abilities in the deepening of Microsoft . From the development of the student's comprehension, a data analysis will be drawn which will then be described in descriptive analysis. The results of training showed that many of the students had little understanding of the learning material so far due to their rarity in carrying out parkatek activities. The enthusiasm of students is also very high as long as students receive this material and learning activities together.